Analyzing Company Value in Indonesian Pharmaceuticals and Health Care Research Companies - Zulkifli, Zulkifli; Dewi, Cynthia Sari (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The development of pharmaceutical and health care research companies shows positive dynamics, driven by innovation, digitalization, supportive regulations, and increased health awareness among the public. Companies continue to adapt to market and technological changes to remain competitive and relevant in both domestic and international markets while responding to evolving global health challenges. The aim of this study is to analyze the return on assets (ROA) and debt-to-equity ratio (DER) in relation to price-to-book value (PBV). This research uses a quantitative approach. The population consists of 13 companies. The sample was determined using purposive sampling, resulting in 10 companies that met the research criteria. Data analysis was conducted using multiple linear regression analysis. The results show that ROA and DER each have a positive and significant impact on PBV. These findings highlight the importance of effective asset management to improve ROA as well as optimal debt management to maximize the use of equity and investments. Enhancing operational performance and efficient asset utilization can increase company value with the PBV indicator, which encourages company to focus on profitability in order to increase their competitiveness and relevance in both domestic and international markets